SYSTEMATIC LITERATURE REVIEW: APPLICATION-BASED LEARNING MEDIA TO MEASURE MATHEMATICAL CRITICAL THINKING ABILITY - Mufida, Naila Rahma; Arfinanti, Nurul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2025)
In this modern era, the world's population is now faced with the need to balance technological advances with knowledge, this is reflected in the development and improvement of technical abilities and skills of today's humans through the development of technology that continues to grow. One form of its implementation in the world of education is the use of application-based learning media. The use of application-based learning media is used to improve students' abilities, one of which is the ability to think critically mathematically. This study aims to determine the use of application-based learning media to measure mathematical critical thinking skills. The method used in this study is SLR (Systematic Literature Review) where researchers collect articles related to the use of learning applications to measure critical thinking skills with a publication period of 2020-2023. Based on this study, it was found; 1) applications as learning media have definitions, objectives, important roles in the field of education, and 2) there is a significant influence in the use of applications on students' critical thinking skills.